Intermittent Optogenetic Tachypacing of Atrial Engineered Heart Tissue Induces Only Limited Electrical Remodelling. Issue 3 (March 2021) - Lemoine, Marc D.; Lemme, Marta; Ulmer, Bärbel M.; Braren, Ingke; Krasemann, Susanne; Hansen, Arne; Kirchhof, Paulus; Meyer, Christian; Eschenhagen, Thomas; Christ, Torsten
Abstract : Abstract: Atrial tachypacing is an accepted model for atrial fibrillation (AF) in large animals and in cellular models. Human induced pluripotent stem cells-derived cardiomyocytes (hiPSC-CM) provide a novel human source to model cardiovascular diseases. Here, we investigated whether optogenetic tachypacing of atrial-like hiPSC-CMs grown into engineered heart tissue (aEHT) can induce AF-remodeling. After differentiation of atrial-like cardiomyocytes from hiPSCs using retinoic acid, aEHTs were generated from ∼1 million atrial-like hiPSC-CMs per aEHT. AEHTs were transduced with lentivirus expressing channelrhodopsin-2 to enable optogenetic stimulation by blue light pulses. AEHTs underwent optical tachypacing at 5 Hz for 15 seconds twice a minute over 3 weeks and compared with transduced spontaneously beating isogenic aEHTs (1.95 ± 0.07 Hz). Force and action potential duration did not differ between spontaneously beating and tachypaced aEHTs. Action potentials in tachypaced aEHTs showed higher upstroke velocity (138 ± 15 vs. 87 ± 11 V/s, n = 15–13/3; P = 0.018), possibly corresponding to a tendency for more negative diastolic potentials (73.0 ± 1.8 vs. 68.0 ± 1.9 mV; P = 0.07). Tachypaced aEHTs exhibited a more irregular spontaneous beating pattern (beat-to-beat scatter: 0.07 ± 0.01 vs. 0.03 ± 0.004 seconds, n = 15–13/3; P = 0.008). Targeted expression analysis showed higher RNA levels of KCNJ12 [Kir2.2, inward rectifier (IK1 ); 69 ± 7 vs. 44 ± 4, P = 0.014] and NPPB (NT-proBNP; 39, 690 ± 4834 vs. 23, 671 ± 3691; P = 0.024). Intermittent tachypacing in aEHTs induces some electrical alterations found in AF and induces an arrhythmic spontaneous beating pattern, but does not affect resting force. Further studies using longer, continuous, or more aggressive stimulation may clarify the contribution of different rate patterns on the changes in aEHT mimicking the remodeling process from paroxysmal to persistent atrial fibrillation. Abstract : Supplemental Digital Content is Available in the Text.